PEMBINAAN KOPERASI OLEH DINAS KOPERASI, UKM DAN PEMBERDAYAAN MASYARAKAT KOTA DUMAI DI KECAMATAN MEDANG KAMPAI TAHUN 2016- 2017 - Ismail Ade Putra; Erman Muchtar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The research present describe the coaching Cooperation by Cooperation, UKM and Society Empowerment Agency Dumai City in Medang Kampai District in 2016-2017. One of economic activity in Indonesia based on the constitution articles 33 are economic based on families effort. Cooperative are one of economic intitutions that have purposed to support economic society, however untill now cooperative in Dumai City are non documented by activeated.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Medang Kampai District Dumai City and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head Agency of Coperation, micro small and middle Dumai City, Head of Coaching Cooperative Dumai City and staff of coperation in Medang Kampai district.The conclution of this research are the coaching Cooperation by Cooperation, UKM and Society Empowerment Agency Dumai City in Medang Kampai District are have done by some activity likes give some regulation and guidelines standart operational procedure by intern and extern, give some supervised and consultating about cooperations and training educations for staff cooperation in Dumai City by persuasive and preventive. Some factors that cause the coaching Cooperation by Cooperation, UKM and Society Empowerment Agency Dumai City in Medang Kampai District are not optimall are low of human resources quality in Coperation, micro small and middle Dumai City, low of participation and communication between staff in Coperation, micro small and middle Dumai City.Keywords: coaching, institutions and coperation.